Dampak Penghapusan Ketentuan Pidana Pencemaran Limbah B3 Oleh Korporasi Industri Kelapa Sawit Dalam Undang-Undang Nomor 6 Tahun 2023 Tentang Cipta Kerja - Rahmi Wijaya, Annisa; Yandriza; Tenofrimer (Delicti : Jurnal Hukum Pidana Dan Kriminologi, 2024)
The Palm Oil industry produces Hazardous and Toxic Waste (B3). However, along with the development of legal regulations in Indonesia, Law Number 6 of 2023 concerning Cipta Kerja was born. This legal reform has an impact on several changes in a statutory provision, one of which is the provision regarding the environment. One of the changes in the ratification of the Job Creation Law is the elimination of criminal sanctions for environmental crimes which are replaced with administrative sanctions. The provisions in the Job Creation Law that abolish Article 102 of the UUPPLH where the abolition of this article can no longer be subject to criminal liability to any person who manages B3 waste without a permit. The research used is normative legal research  using the Status Approach. This research is descriptive in nature which is organized systematically. The results of the study state that the impact of the palm oil industry on B3 waste pollution provides convenience for corporations, but reduces the quality of life of the surrounding community. This also affects environmental legal protection, such as the lack of deterrent effects, non-optimal ecological recovery, and poor environmental supervision. With the Cipta Kerja Law, corporations are only subject to administrative sanctions for such violations